Avaliação de impacto do projeto jovem de futuro no Ceará - Macedo, Sandra Valéria Araújo (2017)
Improving education quality in public high schools is considered a major bottleneck for Brazilian educational system, which needs immediate actions, so as to keep youngsters at school and enhance their cognitive skills. Policymakers are well aware that low stagnant college students’ performance undermines the country’s competitivity and sustainability. In such a context, a programme called “Jovem de Futuro” appears as a public-private partnership proposal. Focusing on a result-based school management model, the project Incorporates scientific knowledge and uses an experimental design to enable impact evaluation. The project was tested on the states of Sao Paulo, Rio de Janeiro, Minas Gerais and Rio Grande do Sul, and, after that, it became a public policy which was then implemented in some states of the country, among which, Ceara. This work aims to evaluate the impact of “Jovem do Futuro” in the state of Ceara, on its 2nd implementation run, from 2013 to 2015, when 123 public schools were benefited from the programme. The empirical strategy used a quantilic regression model to estimate the effects on Maths and Portuguese’s individual tests scores from SPAECE. The results were positive, however, there was some heterogeneity on the different quantile conditional distribution for both subjects’ scores, where major effects were seen on Math’s scores upper quantiles, and, on distribution tails for Portuguese’s scores, especially the lower ones. With respect to the project implementation level, associated to the number of methodologies chosen by treatment schools, the results were not clear; for instance, with as much relevant impact for schools who took many sub-programs, as for those who did not incorporate any of the new practices, which points out, once more, that the main issue may not be related to program scale, but to project implementation.